Estimating the costs associated with the implementation of a best practice model of care for recurrent miscarriage clinics in Ireland: a cost analysis [version 1; peer review: 1 approved, 2 approved with reservations] - Keelin O'Donoghue; Caragh Flannery; Paddy Gillespie; Lee-Ann Burke (HRB Open Research, 2022)
Background  Recurrent miscarriage (RM) affects 1%-5% of the reproductive age population. Given increasing calls for dedicated recurrent miscarriage clinics (RMC), decision makers will require data on the resultant budgetary implications. The aim of this study was to identify the potential costs to the Irish healthcare system of implementing a best practice RMC model of care.    Methods  A ‘best practice’ RMC was developed as part of the RE:CURRENT Project. A micro-costing approach was employed by identifying, measuring, and valuing resource usage by unit costs for the RMC for ≥2 consecutive losses. Per patient costs were estimated using two care pathway scenarios: typical and complex. Per patient costs were extrapolated, using population data and published prevalence rates for RM, to estimate the total cost to the Irish health system. A sensitivity analysis was also performed.     Results   The cost for a RM patient who has another pregnancy after receiving investigations, treatment and reassurance scans ranges between €1,634 (typical) and €4,818 (complex). For a RM patient who does not conceive again, costs range from €1,384 (typical) to €4,318 (complex). Using population estimates for ≥2 losses, the total cost to the Irish health service ranges from €20,336,229 (complex) to €61,927,630 (typical) for those who progress to pregnancy, and from €7,789,437 (complex) to €22,480,630 (typical) for those who do not progress to another pregnancy. Together, the total cost of the proposed best practice RMC is €112,533,926 with an average cost per patient €1,871.     Conclusions  This study advocates for a new model of care for RMCs in Ireland and provides a set of cost estimates at the patient and healthcare system level. While future studies should explicitly consider the cost effectiveness of this or similar models of care, this analysis provides a valuable first step in providing a detailed breakdown of the associated costs and budget implications.